Answer:
(-1, 5)
(0, 3)
(2, -1)
Step-by-step explanation:
we have
![f(x)=3-2x](https://tex.z-dn.net/?f=f%28x%29%3D3-2x)
Remember that
If a ordered pair is a solution of the given function, then the ordered pair must satisfy the given function
<u><em>Verify each case</em></u>
case a) (-2, -1)
substitute the value of x and the value of y in the given function and compare the result
![-1=3-2(-2)](https://tex.z-dn.net/?f=-1%3D3-2%28-2%29)
---> is not true
therefore
Is not a ordered pair of the given function
case b) (-1, 5)
substitute the value of x and the value of y in the given function and compare the result
![5=3-2(-1)](https://tex.z-dn.net/?f=5%3D3-2%28-1%29)
---> is true
therefore
Is a ordered pair of the given function
case c) (0, 3)
substitute the value of x and the value of y in the given function and compare the result
![3=3-2(0)](https://tex.z-dn.net/?f=3%3D3-2%280%29)
---> is true
therefore
Is a ordered pair of the given function
case d) (1,0)
substitute the value of x and the value of y in the given function and compare the result
![0=3-2(1)](https://tex.z-dn.net/?f=0%3D3-2%281%29)
---> is not true
therefore
Is not a ordered pair of the given function
case e) (2, -1)
substitute the value of x and the value of y in the given function and compare the result
![-1=3-2(2)](https://tex.z-dn.net/?f=-1%3D3-2%282%29)
---> is true
therefore
Is a ordered pair of the given function